(untitled) (Zaporizhzhia Historical Review, 2021)
The article is devoted to the problem of formation of the American concept of unification of Germany. The author on the basis of public papers of the president the USA George Bush examines his position in a question of Germany participation in the NATO, the solution of a problem of borders, the main conditions of unification between FRG and NDR and states the idea about the basis of relations " partnership in leadership " between Germany and the USA.